Globalisation contested : an international political economy of work - Amoore, Louise (Manchester University Press : Distributed exclusively in the USA by Palgrave, 2002)
Bringing fresh insights to the contemporary globalization debate, this text reveals the social and political contests that give "global" its meaning, by examining the contested nature of globalization as it is expressed in the restructuring of work.